2013
DOI: 10.1016/j.visres.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spatial offset, temporal offset and image speed on sensitivity to global motion in human amblyopia

Abstract: The presence of a general global motion processing deficit in amblyopia is now well established, although its severity may depend on image speed and amblyopia type, but its underlying cause(s) is still largely indeterminate. To address this issue and to characterize further the nature of the global motion perception deficit in human amblyopia, the effects of varying spatial offset (jump size-Δs) and temporal offset (delay between positional updates-Δt) in discriminating global motion for a range of speeds (1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…As a whole, this body of work suggests that binocular interactions may play a key role in strabismic and anisometropic amblyopia (Hess et al, 2011; Hess and Thompson, 2013). This is consistent with a number of studies reporting less pronounced elevations in monocular motion coherence thresholds for amblyopic observers with residual binocular function (Ho et al, 2005; Knox et al, 2013). The question of whether suppression also plays a role in deprivation amblyopia is still open; however, very recent measurements made in our laboratory suggest that suppression is measureable in at least some cases of deprivation amblyopia using the dichoptic RDK technique.…”
Section: Global Deficits In Amblyopiasupporting
confidence: 92%
See 1 more Smart Citation
“…As a whole, this body of work suggests that binocular interactions may play a key role in strabismic and anisometropic amblyopia (Hess et al, 2011; Hess and Thompson, 2013). This is consistent with a number of studies reporting less pronounced elevations in monocular motion coherence thresholds for amblyopic observers with residual binocular function (Ho et al, 2005; Knox et al, 2013). The question of whether suppression also plays a role in deprivation amblyopia is still open; however, very recent measurements made in our laboratory suggest that suppression is measureable in at least some cases of deprivation amblyopia using the dichoptic RDK technique.…”
Section: Global Deficits In Amblyopiasupporting
confidence: 92%
“…Furthermore, this deficit is not reliant on the spatial properties of the dots within the RDKs (Aaen-Stockdale and Hess, 2008) and is not dependent on the relative spatial and temporal offsets of the dots (Knox et al, 2013). A number of studies also observed deficits in fellow eyes relative to control eyes supporting Simmers et al’s (2003) original finding (Ho et al, 2005; Aaen-Stockdale and Hess, 2008).…”
Section: Global Deficits In Amblyopiamentioning
confidence: 99%
“…These findings support the theory that both microsaccades and exploratory saccades have a common neurophysiologic basis. 4,46,47 Previous studies have reported abnormalities in the fellow and amblyopic eye including reduced contrast, 13,14,48,49 spatial integration, [50][51][52][53] global motion, [54][55][56][57] and motion-perception. [58][59][60] These studies did not categorize patients with and without LN.…”
Section: Discussionmentioning
confidence: 99%
“…The amblyopic eye of observers shows deficits in global motion perception relative to controls 196,[220][221][222][223][224] though this deficit is not robust-some studies have found no deficits in the amblyopic eye. 40,197 This may depend on stimulus parameters, because not all global motion stimuli elicit abnormal coherence thresholds in amblyopia.…”
Section: Global Motion Perception Deficits In the Amblyopic Eyementioning
confidence: 99%